Let x ≥ 0 and y ≥ 0 .
If x 2 1 = 1 6 1 − x y 1 and y 2 1 = 2 1 − x y 1 , find x y .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We have 1 6 y = x 2 y − 1 6 x , 2 x = x y 2 − 2 y
1 6 ( x + y ) = x 2 y = 8 x y 2 , x = 8 y
x 2 1 = 8 x y 1 = 1 6 1 − x y 1
Let x y 1 = z , then 8 1 z = 1 6 1 − z , z = 1 8 1 , x y = 1 8
May need some parentheses in the second line. Looks like you are multiplying 16 by x and then adding y.
Problem Loading...
Note Loading...
Set Loading...
Multiplying the two equations, we get:
x 2 y 2 1 = ( 1 6 1 − x y 1 ) ( 2 1 − x y 1 )
( x y 1 ) 2 = ( 1 6 1 − x y 1 ) ( 2 1 − x y 1 )
Let u = x y 1
The result can be then rewritten as:
u 2 = ( 1 6 1 − u ) ( 2 1 − u )
Solving for u:
u 2 = 3 2 1 − 1 6 9 u + u 2
0 = 3 2 1 − 1 6 9 u
0 = 1 − 1 8 u
u = 1 8 1
Substituting back the definition of u:
x y 1 = 1 8 1
Taking the reciprocal of both sides gives us our final answer:
x y = 1 8